OPEN BIDDING JABATAN DALAM UPAYA MENJARING PIMPINAN KEARSIPAN YANG PROFESIONAL: Array - Sumrahyadi Sumrahyadi (Jurnal Kearsipan, 2013)
The idea of open bidding for some officers in government employees as a public servant actually is very good concept. However, the appointment criteria and standard minimum to the qualified positions is demanded. An independent consultant for selecting a competent and profesional employee as a leader of the position to be the best officer is required. Similarly, for the top manager of Archival position or level one position (Deputy and Director General) at The National Archives of Indonesia, the candidates must have the ability to both manage records and archives activities profesionally and have the capacity as a top manager. The political and other vested interests should be avoided to acquire best leader for archival institutions.